Phoresy and Within-colony Transmission of Nematodes Associated with Alates of Subterranean Termites (Isoptera: Rhinotermitidae). Issue 5 (26th June 2018) - Foley, Jeremiah R; Chouvenc, Thomas; Giblin-Davis, Robin M; Su, Nan-Yao; Kanzaki, Natsumi
Abstract: Termites and their nests are potential resources for a wide assemblage of taxa including nematodes. During dispersal flight events from termite colonies, co-occurring nematodes in the nest may have phoretic opportunities to use termite alates as transportation hosts. The two subterranean termite species Coptotermes gestroi (Wasmann) and Coptotermes formosanus Shiraki are both invasive and established in south Florida. Alates of both species ( n = 245) were collected during dispersal flight events in 2015–2016 from six locations, of which 30 (12.2%) were associated with one or more species of nematodes. Species of Bunonema Jägerskiöld (Rhabditida: Bunonematidae), Halicephalobus Timm (Rhabditda: Panagrolaimidae), and Poikilolaimus regenfussi (Sudhaus) Sudhaus and Koch (Rhabditida: Rhabditidae) were isolated from 5.3, 4.9, and 0.4% of termite alates, respectively, and Bunonema and Halicephalobus were concomitant in 1.6% of alates. Additional C. formosanus alates were field-collected to establish laboratory colonies in sterilized rearing containers (SRC) to determine if alate-associated nematodes would colonize the newly established nest and/or brood. Among 1-yr-old termite colonies reared in SRCs, 26.9% of the colonies were positive for nematodes confirming that within-colony transmission of nematodes occurred. All three isolated nematode genera are free-living bacterivores capable of asexual reproduction. This suggests that these common co-occurring, termite-associated nematodes are opportunistic and facultative symbionts that receive increased opportunities of geographical dispersion through phoresy during termite dispersal flight events.